Silicon dioxide aerogel powder material and preparation method thereof

The silica aerogel powder material prepared by the acid-base two-step catalytic method solves the problem of insufficient insulation performance of traditional sleeves, achieves low-cost and efficient thermal insulation effect, and is suitable for the efficient utilization of geothermal resources.

CN119461391APending Publication Date: 2025-02-18CHINA NAT PETROLEUM CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411626334.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the utilization efficiency of geothermal resources is lower than expected, mainly due to the insufficient insulation performance of traditional casing, which leads to large heat loss during hot water extraction. In addition, existing energy-saving insulation materials have loose fiber structures, easy to absorb moisture, and fire. Risk issues.

Method used

The hydrolyzed condensation product was prepared by alkoxysilane by two-step acid-base catalytic method, and a silica aerogel powder material with low thermal conductivity was prepared through gelation, aging, solvent exchange, drying and grinding steps.

Benefits of technology

It realizes low-cost, low thermal conductivity, low density, low moisture absorption and high performance silica aerogel powder material, suitable for heat insulation sleeves, maximizes and reduces thermal energy loss, improves heat conduction efficiency, and reduces geothermal mining costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461391A_ABST
    Figure CN119461391A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal insulation materials, in particular to a silicon dioxide aerogel powder material and a preparation method thereof. The preparation method comprises the following steps: preparing a hydrolytic condensation product from alkoxy silane through an acid-base two-step catalysis method, and carrying out gelation, aging, solvent exchange, drying and grinding on the hydrolytic condensation product to obtain the silicon dioxide aerogel powder material, in the acid-base two-step catalysis method, an acid catalyst is acetic acid, a base catalyst is urea, and the particle size range of the silicon dioxide aerogel powder material is 0.5-1 mm. The silicon dioxide aerogel powder material obtained through the method is good in heat insulation effect and suitable for pipeline heat insulation, the method has the advantages of being low in cost, ultra-light in weight and high in performance, and the practical effect is better than that of a traditional heat preservation and insulation material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal insulation materials, and in particular to a silicon dioxide aerogel powder material and a preparation method thereof. Background Art

[0002] Geothermal energy is an environmentally friendly clean energy. my country has abundant geothermal resources. Fully utilizing geothermal resources is of great significance to energy conservation and emission reduction. The utilization efficiency of medium and low temperature geothermal resources is closely related to the underground insulation process. Traditional casing does not have insulation performance, resulting in large heat loss along the hot water extraction process, which greatly reduces the utilization efficiency of geothermal resources and affects their use value.

[0003] In recent years, with the continuous development of the technological level of my country's material processing industry, thermal insulation materials have also made great progress and development. The main energy-saving thermal insulation materials on the market, such as rock wool, glass wool and other inorganic fiber wool, have problems such as loose fiber structure and easy moisture absorption. The thermal insulation performance will drop significantly during the use cycle. Organic thermal insulation materials such as polystyrene and polyurethane foam have fire risks. The new silica aerogel thermal insulation material has many excellent properties such as low thermal conductivity, good thermal insulation performance, stable physical and chemical properties, high temperature non-flammable, completely waterproof, non-toxic, green and environmentally friendly. At present, some high-temperature steam pipelines and direct buried steam pipeline projects have taken the lead in using it. The application forms of silica aerogel mainly include aerogel coatings, aerogel felt pads, aerogel sheets, aerogel concrete and mortar. Although there are application cases of silica aerogel in industrial storage tanks and pipelines, it has not been widely promoted in this field, and further optimization is needed in terms of material performance and cost.

[0004] Therefore, there is an urgent need for an aerogel insulation material that uses a low-cost freeze-drying process to replace the supercritical drying process and optimizes the pores and particle size to meet the technical requirements of efficient and low-cost insulation casings, maximize the reduction of heat loss along the transmission process, improve the efficiency of heat conduction, and reduce the comprehensive cost of geothermal exploitation. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a silica aerogel powder material and a preparation method to solve the problems of high thermal conductivity, high density, high cost and poor thermal insulation effect of the material in the prior art.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] The present invention provides a method for preparing a silica aerogel powder material, which comprises using alkoxysilane to prepare a hydrolysis condensation product through an acid-base two-step catalytic method, and then subjecting the hydrolysis condensation product to gelation, aging, solvent exchange, drying and grinding to obtain the silica aerogel powder material.

[0008] Among them, in the acid-base two-step catalytic method, the acid catalyst is acetic acid, the base catalyst is urea, and the mass volume ratio of the alkoxysilane, acetic acid and urea is in the range of 0.5-2mL: 0.126-0.484mg: 1-2.5g.

[0009] Based on the above technical solution, the present invention can also be improved as follows.

[0010] Furthermore, the alkoxysilane is tetramethoxysilane, tetraethoxysilane, vinyltrimethoxysilane or methyltrimethoxysilane.

[0011] Furthermore, the alkoxysilane is methyltrimethoxysilane; the steps of the acid-base two-step catalytic method are as follows: a surfactant, urea and water are mixed to prepare an alkaline catalyst solution; after the methyltrimethoxysilane solution is mixed with the acetic acid solution, the alkaline catalyst solution is added until the pH value of the solution is 8.5-9.5, and ultrasonic treatment is performed at a temperature of 30°C-50°C to obtain the hydrolysis condensation product.

[0012] Furthermore, the surfactant is trimethyl 1-hexadecyl ammonium bromide, and the mass volume ratio of trimethyl 1-hexadecyl ammonium bromide, urea and water is 0.1-0.3g:1-2.5g:2.5-10mL.

[0013] Furthermore, in the methyltrimethoxysilane solution, the mass percentage of methyltrimethoxysilane is 97%-99%; in the acetic acid solution, the mass percentage of acetic acid is 0.8%-1.2%; and the volume ratio of the methyltrimethoxysilane solution to the acetic acid solution is 1:0.028-0.029.

[0014] Furthermore, the solvent exchange step is to soak the aged product in deionized water, anhydrous ethanol and isopropanol respectively, with each soaking time being 2-6 hours.

[0015] Furthermore, the aerogel material obtained after drying has a specific surface area of ​​600-1000 and an average pore size of 10nm-20nm.

[0016] The present invention also provides a silicon dioxide aerogel powder material, which is prepared by the above method.

[0017] Furthermore, the particle size of the silica aerogel powder material ranges from 10 μm to 2 mm.

[0018] The present invention also provides a heat-insulating sleeve, which is prepared by using the above-mentioned silica aerogel powder material.

[0019] The beneficial effects of the present invention are:

[0020] (1) The method for preparing the silica aerogel powder material of the present invention prepares the hydrolysis condensation product by the acid-base two-step catalytic method. By reasonably preparing the amount of each raw material, the aerogel with low thermal conductivity can be prepared by the low-cost sol-gel method;

[0021] (2) The preparation method of the silica aerogel powder material of the present invention controls the particle size range of the silica aerogel powder material to be 0.5-1 mm, so that the thermal insulation effect is optimal and it is most suitable for practical application in pipeline thermal insulation;

[0022] (3) The preparation method of the silica aerogel powder material of the present invention has the advantages of low cost, ultra-light weight and high performance, and its practical effect is better than that of traditional thermal insulation materials;

[0023] (4) The silica aerogel powder material of the present invention has the advantages of low thermal conductivity, low density, low moisture absorption, and low cost;

[0024] (5) The silica aerogel powder material of the present invention is particularly suitable for use in thermal insulation casings, meeting the technical requirements of high-efficiency and low-cost thermal insulation casings, minimizing the loss of heat energy along the transmission process, improving the efficiency of heat conduction, and reducing the comprehensive cost of geothermal exploitation. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The method for preparing the silica aerogel powder material of the present invention is a flow chart of Example 1;

[0026] Figure 2 This is a method for preparing a silica aerogel powder material of the present invention, and a microscopic morphology of a silica aerogel material prepared in Example 1;

[0027] Figure 3 This is a method for preparing a silica aerogel powder material of the present invention, and an adsorption-desorption curve of the silica aerogel material prepared in Example 1;

[0028] Figure 4 This is a method for preparing a silica aerogel powder material of the present invention, and a pore size distribution diagram of a silica aerogel material prepared in Example 1;

[0029] Figure 5 The method for preparing the silica aerogel powder material of the present invention is a comparison chart of the average pore size of the aerogel after adjusting the content of MTMS in Example 2;

[0030] Figure 6 The method for preparing the silica aerogel powder material of the present invention is shown in Figure 3, which shows silica aerogel powder materials with different particle sizes. Figure 6The particle size range of a is 0.2-0.5mm. Figure 6 The particle size range of medium b is 0.5-1mm, Figure 6 The particle size range of medium c is 1-2mm, Figure 6 The particle size range of medium d is greater than 2 mm;

[0031] Figure 7 The method for preparing the silica aerogel powder material of the present invention is a bar graph showing the thermal conductivity and density changes of the silica aerogel powder materials with different particle sizes prepared in Example 3;

[0032] Figure 8 This is a comparison chart of the overall thermal conductivity and density of the silica aerogel powder material prepared in the method for preparing the silica aerogel powder material of the present invention with the silica aerogel powder material having a particle size range of 0.5 mm-1 mm prepared in Example 3 and other commonly used thermal insulation materials. DETAILED DESCRIPTION

[0033] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0034] The method for preparing a silica aerogel powder material of the present invention comprises the following steps: using alkoxysilane to prepare a hydrolysis condensation product through an acid-base two-step catalytic method, and then subjecting the hydrolysis condensation product to the steps of gelation, aging, solvent exchange, drying and grinding, so as to obtain the silica aerogel powder material; wherein in the acid-base two-step catalytic method, the acid catalyst is acetic acid, the base catalyst is urea, and the mass volume ratio of alkoxysilane, acetic acid and urea is in the range of 0.5-2 mL: 0.126-0.484 mg: 1-2.5 g.

[0035] The method for preparing the silica aerogel powder material of the present invention prepares the hydrolysis condensation product by an acid-base two-step catalytic method, and by reasonably preparing the dosage of each raw material, an aerogel with low thermal conductivity can be prepared by a low-cost sol-gel method.

[0036] Preferably, the alkoxysilane is tetramethoxysilane, tetraethoxysilane, vinyltrimethoxysilane or methyltrimethoxysilane; these alkoxysilanes provide a versatile means of introducing functional moieties, either by including a co-transmitter in the initial mixture or by later surface modification, and allow for easy control of the final structure.

[0037] Preferably, the alkoxysilane is methyltrimethoxysilane; the steps of the acid-base two-step catalytic method are as follows: a surfactant, urea and water are mixed to prepare an alkaline catalyst solution; after the methyltrimethoxysilane solution is mixed with the acetic acid solution, the alkaline catalyst solution is added until the pH value of the solution is 8.5-9.5, and ultrasonic treatment is performed at a temperature of 30°C-50°C to obtain a hydrolysis condensation product.

[0038] Preferably, the surfactant is trimethyl 1-hexadecyl ammonium bromide, and the mass volume ratio of trimethyl 1-hexadecyl ammonium bromide, urea and water is 0.1-0.3 g:1-2.5 g:2.5-10 mL.

[0039] Further preferably, the mass volume ratio of trimethyl 1-hexadecyl ammonium bromide, urea and water is 0.2 g:1.5 g:5 mL, which is the best ratio and is conducive to the reaction process from sol to gel and the formation of network structure.

[0040] Trimethyl 1-hexadecyl ammonium bromide (CTAB) is a surfactant whose functions include improving particle dispersibility, preventing precipitation, adjusting pore structure and enhancing skeleton strength.

[0041] Preferably, in the methyltrimethoxysilane solution, the mass percentage of methyltrimethoxysilane is 97%-99%; in the acetic acid solution, the mass percentage of acetic acid is 0.8%-1.2%; and the volume ratio of the methyltrimethoxysilane solution to the acetic acid solution is 1:0.028-0.029.

[0042] The hydrolysis and condensation process of the present invention is to generate active hydroxyl groups by hydrolyzing the precursor molecules. After hydrolysis, the precursor molecules form siloxane bridges through multiple condensation reactions, and primary particles (particle size <1nm) are nucleated and aggregated into secondary particles (tens of nanometers in size) to form a sol. Since the partial positive charge of silicon atoms in the silanoxysilane precursor is relatively low (δ Si =+0.32), compared with other metal alkoxides, at neutral pH and ambient temperature, the hydrolysis and condensation reactions are very slow. Therefore, the method of the present invention adopts an acid and base two-step catalytic process to be controlled separately, in which the acid catalysis is conducive to the hydrolysis reaction, and the subsequent transition to alkaline conditions is conducive to the condensation reaction.

[0043] Under acidic conditions, due to the more favorable hydrolysis of siloxane bonds, silica particles tend to form linear chains with low cross-linking density, which are easy to break; while under higher pH conditions, the gel matrix is ​​more likely to form a cross-linked structure with branches. When the condensation process reaches the entire sol volume, gelation (through condensation) occurs. In addition, the mechanical state of the gel depends largely on the number of cross-links in the network, so the pH value will also affect the mechanical properties of the gel.

[0044] The method of the present invention can achieve the regulation of aerogel porosity by regulating the specific amount of water, pH value and catalyst, and further achieves the regulation of aerogel specific surface area and pore size and distribution. According to the infinite path theory of heat transfer, the larger the specific surface area, the smaller the pore size and the more uniform the distribution, the better the thermal insulation performance of the aerogel.

[0045] Preferably, in the method of the present invention, the pH value of gelation is 4-10 and the temperature is 60°C.

[0046] The process of gelation is that smaller fragments dissolve and redeposit onto larger chains, thereby reducing the number of smaller molecules but helping larger molecules grow until fractal aggregates are formed. This process is called Ostwald ripening. When the condensation process reaches the entire volume of the sol, gelation (by polycondensation) occurs as primary particles aggregate onto secondary particles, which then connect to form a three-dimensional network with a pearl necklace-like structure. For the preparation of aerogels, gelation is most easily induced by changing the pH value of the reaction solution. Gelation needs to be carried out at a high temperature of 60°C. In order to heat it evenly and gel it better, it is generally placed in a special sealed mold and placed in deionized water.

[0047] Preferably, in the method of the present invention, the aging temperature is 60° C. and the time is 2-5 days.

[0048] Specifically, the aging method is to soak the gel in deionized water at 60°C to enhance the strength of the gel and reduce the risk of skeleton collapse and shrinkage during the drying process.

[0049] Preferably, in the method of the present invention, the solvent exchange step is to soak the aged product in deionized water, anhydrous ethanol and isopropanol respectively, and each soaking time is 2-6 hours. The purpose of solvent exchange is to remove impurities and solvents in the gel, adjust the pore size and porous structure, and enhance the hydrophobicity and mechanical properties of the material.

[0050] Preferably, in the method of the present invention, the drying method is supercritical drying, freeze drying or atmospheric pressure drying.

[0051] The purpose of drying is to remove the liquid in the pores while keeping the three-dimensional skeleton structure of the gel intact. Among them, the supercritical high-pressure drying process has a high technical threshold and good drying effect, but the cost is difficult to control and the output is limited; freeze-drying technology is usually used in industrial production. Its principle is to freeze the liquid in the pores and then sublimate it in a vacuum for drying. Its preparation cost is relatively low and it can be mass-produced. Its disadvantage is that the network may be destroyed by the crystallization of the solvent in the pores. Therefore, the freezing method is more suitable for the preparation of aerogel powders.

[0052] Preferably, the aerogel material obtained after drying has a specific surface area of ​​600-1000 and an average pore size of 10nm-20nm; the aerogel material has good thermal insulation performance.

[0053] Preferably, in the method of the present invention, the grinding method is manual grinding, mechanical grinding or air flow grinding.

[0054] The particle sizes obtained by the above three methods decrease in sequence. Air flow milling can obtain aerogel powder with a particle size of 10 μm, but the corresponding cost will increase; manual grinding can obtain aerogel powder with a particle size ranging from 0.2 mm to 2 mm.

[0055] The method of the present invention not only prepares a silica aerogel powder material with good thermal insulation effect, but also has the advantages of low cost, ultra-light weight and high performance, and its practical effect is better than that of traditional thermal insulation materials.

[0056] Compared with traditional thermal insulation materials (such as glass wool and glass fiber), the silica aerogel powder material of the present invention has a significantly lower thermal conductivity, which can be lower than 0.02W / (m·K), has the advantages of high thermal insulation and high stability, greatly improved thermal insulation performance and significantly reduced weight.

[0057] Preferably, the particle size range of the silica aerogel powder material of the present invention is 0.5-1 mm. According to specific experimental results, it is found that the smaller the particle size, the better the thermal insulation effect. When the particle size is too small, the thermal conductivity will increase. Therefore, the particle size range of the present invention has the best thermal insulation effect and is most suitable for practical applications in pipeline insulation.

[0058] Preferably, the silica aerogel powder material of the present invention can reduce density by about 70% compared with traditional thermal insulation materials, and has the advantage of being lightweight.

[0059] The heat-insulating sleeve of the present invention is prepared by adopting the silicon dioxide aerogel powder material of the present invention, and has the advantages of good heat-insulating effect, light weight, low cost, etc.

[0060] The present invention is illustrated below by means of specific examples.

[0061] Example 1 Preparation of Silica Aerogel

[0062] This embodiment adopts the method of the present invention to prepare silica aerogel. Figure 1 As shown, the specific process is as follows:

[0063] Take 0.2g CTAB (trimethyl 1-hexadecyl ammonium bromide), mix with 1.5g urea, fully dissolve in 5ml deionized water, add 1mL 98% MTMS (methyltrimethoxysilane) solution and 28.7μL 1% diluted acetic acid, and place in 60℃ environment for 30min ultrasonication to fully hydrolyze. The above amount of urea can make the pH of the same industry reach 8.5.

[0064] The hydrolysis-condensation product was placed in a sealed mold and placed in deionized water for gelation at a temperature of 60° C. and a pH value of 5.

[0065] The gelled product was immersed in deionized water at 60° C. for aging for 4 days.

[0066] The aged products were immersed in deionized water, anhydrous ethanol and isopropanol respectively, with each immersion time being 5 h.

[0067] The aged product was freeze-dried at a temperature of minus 55°C and a vacuum degree of 10 Pa for 8 hours.

[0068] In this embodiment, the microstructure of the aerogel material obtained after freeze drying is first tested. Figure 2 As shown in the figure, it can be seen that the silica aerogel has a nanoscale microporous structure.

[0069] The silica aerogel of this example has an adsorption-desorption curve and pore size distribution as shown in Figure 3 and Figure 4 As shown, it can be seen that the aerogel is a porous material with rich microporous structure and the pore size is mostly distributed between ten and twenty nanometers. Specifically, the specific surface area of ​​the aerogel material is 777.3, the average pore size is 12.68nm, and the thermal insulation performance is good.

[0070] Example 2 Comparison of pore size distribution of aerogels prepared with different parameters

[0071] In this embodiment, the pore size and specific surface area are controlled by adjusting the ratio of reagents and chemicals used in the synthesis process.

[0072] As for the specific dosage of MTMS, this embodiment uses 0.5mL, 1mL, 1.5mL and 2mL as four control groups, and names them A1-A4. The pore size distribution test results of the prepared aerogel material are as follows:

[0073] The specific surface area of ​​A1 is 850.89, and the average pore diameter is 15.3nm; the specific surface area of ​​A2 is 842.56, and the average pore diameter is 15.637nm; the specific surface area of ​​A3 is 669.82, and the average pore diameter is 19.16nm; the specific surface area of ​​A4 is 777.63, and the average pore diameter is 16.35nm.

[0074] Figure 5 This is a comparison of the average pore size of aerogels after adjusting the MTMS content. It can be explained that by adjusting the content of the precursor, aerogels with different specific surface areas and pore size distributions can be obtained, and then the aerogel with the largest specific surface area and the smallest pore size can be selected. It can be seen from the figure that when the MTMS content is 0.5mL, A1 has the highest specific surface area, the smallest average pore size, and the best theoretical thermal insulation performance. Therefore, we choose aerogels with this pore size distribution as the material for pipeline insulation.

[0075] Example 3 Effect of different powder particle sizes on thermal insulation effect

[0076] In this example, the silica aerogel material obtained in Example 1 was ground. In order to compare the thermal insulation effects of various particle size ranges, powders of various particle size ranges were obtained by different grinding methods, and the thermal insulation effects and thermal conductivity and other properties of these powders were tested and compared.

[0077] The test method is the heat flow meter method, which is a common method for steady-state testing of thermal conductivity. The principle is to establish a constant temperature difference between the upper and lower surfaces of the sample, and form a stable temperature gradient inside the sample when the steady state is reached. The thermal conductivity of the sample is calculated by detecting the heat flow through the sample and combining it with Fourier's heat transfer law. The test instrument used in this embodiment is the NETZSCH HFM 446 Lambda series heat flow method thermal conductivity meter.

[0078] In this embodiment, thermal conductivity and density of five particle size ranges were tested. Figure 6 Aerogel particles of different sizes are obtained by manual grinding, with particle sizes ranging from 0.2mm to 2mm. Figure 7 It is a bar graph of thermal conductivity and density changes of aerogel composites with different particle sizes.

[0079] according to Figure 6 and Figure 7 It can be seen that the hand-ground aerogel has a particle size range greater than 2mm and an average thermal conductivity of 0.0192; the aerogel with a particle size range of 1-2mm has an average thermal conductivity of 0.0158; the aerogel with a particle size range of 0.5-1mm has the lowest average thermal conductivity of 0.0157; the aerogel with a particle size range of 0.2-0.5mm has a slightly higher average thermal conductivity of 0.0163; the ultrafine aerogel obtained by air flow grinding (particle size range of about 10μm) has an average thermal conductivity of 0.0201. In addition, the density of the aerogel obtained by hand-grinding is about 40% lower than that of the ultrafine aerogel, and can be reduced by about 70% compared to the density of traditional insulation materials. In comparison, the aerogel with a particle size range of 0.5-1mm has the best thermal insulation effect and is most suitable for practical applications in the above-mentioned pipeline insulation.

[0080] At the same time, the test shows that the thermal conductivity of aerogel particles with a particle size between 0.5-1mm reaches 0.0157W / (m·K), which is 51% lower than that of traditional insulation materials (such as glass wool and glass fiber). Compared with the same type of aerogels with different particle sizes, the thermal conductivity of aerogels with a particle size of 0.5-1mm is 21% lower than that of ultrafine powder aerogels.

[0081] Figure 8The overall thermal conductivity and density of the silica aerogel powder composite material obtained in this embodiment are compared with other commonly used thermal insulation materials. It can be seen that the silica aerogel powder material of this embodiment has advantages in both thermal conductivity and density, and has the characteristics of low density and low thermal conductivity.

[0082] In the description of the present invention, it should be noted that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0083] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0084] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0085] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0086] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a silica aerogel powder material, characterized in that: The silica aerogel powder material is obtained by using alkoxysilane to prepare a hydrolysis condensation product through an acid-base two-step catalytic method, and then subjecting the hydrolysis condensation product to gelation, aging, solvent exchange, drying and grinding. In the acid-base two-step catalytic method, the acid catalyst is acetic acid, the base catalyst is urea, and the mass volume ratio of the alkoxysilane, acetic acid and urea is in the range of 0.5-2 mL: 0.126-0.484 mg: 1-2.5 g.

2. The method for preparing a silica aerogel powder material according to claim 1, characterized in that: The alkoxysilane is tetramethoxysilane, tetraethoxysilane, vinyltrimethoxysilane or methyltrimethoxysilane.

3. The method for preparing a silica aerogel powder material according to claim 2, characterized in that: The alkoxysilane is methyltrimethoxysilane; the steps of the acid-base two-step catalytic method are as follows: a surfactant, urea and water are mixed to prepare an alkaline catalyst solution; after the methyltrimethoxysilane solution is mixed with the acetic acid solution, the alkaline catalyst solution is added until the pH value of the solution is 8.5-9.5, and ultrasonic treatment is performed at a temperature of 30°C-50°C to obtain the hydrolysis condensation product.

4. The method for preparing a silica aerogel powder material according to claim 3, characterized in that: The surfactant is trimethyl 1-hexadecyl ammonium bromide, and the mass volume ratio of trimethyl 1-hexadecyl ammonium bromide, urea and water is 0.1-0.3g:1-2.5g:2.5-10mL.

5. The method for preparing a silica aerogel powder material according to claim 3, characterized in that: In the methyltrimethoxysilane solution, the mass percentage of methyltrimethoxysilane is 97%-99%; in the acetic acid solution, the mass percentage of acetic acid is 0.8%-1.2%; and the volume ratio of the methyltrimethoxysilane solution to the acetic acid solution is 1:0.028-0.

029.

6. A method for preparing a silica aerogel powder material according to any one of claims 1 to 5, characterized in that: The solvent exchange step is to soak the aged product in deionized water, anhydrous ethanol and isopropanol respectively, with each soaking time being 2-6 hours.

7. A method for preparing a silica aerogel powder material according to any one of claims 1 to 5, characterized in that: The aerogel material obtained after drying has a specific surface area of ​​600-1000 and an average pore diameter of 10nm-20nm.

8. A silica aerogel powder material, characterized in that: The method is prepared by any one of claims 1 to 7.

9. The silica aerogel powder material according to claim 8, characterized in that: The particle size of the silica aerogel powder material ranges from 10 μm to 2 mm.

10. A thermal insulation sleeve, characterized in that: The method is prepared by using the silica aerogel powder material as described in claim 8 or 9.